Membangun Fondasi Iman Anak Melalui Katekese Keluarga - Angelina Febrianty Mukin; Emmeria Tarihoran (Jurnal Magistra, 2024)
This article emphasizes the importance of family catechesis in cultivating faith among children. The utilization of family catechesis can be an effective means of guiding and educating children in religious matters in a complex society that is increasingly influenced by adherence to secular values. Parental involvement is very important in this process. This article discusses the role of family catechesis and the importance of parents in educating children about faith. Use strategies to apply family catechesis to daily life, such as family prayer, reading and discussing scripture, celebrating religious holidays together, leading by example, providing space to ask questions and explore, and using technology and online resources. This article also discusses the challenges that may arise in the implementation of family catechesis, as well as solutions to overcome these challenges. Finally, the conclusion of this article highlights the importance of building a religious foundation for children in an increasingly complex world. Parents have an important role in guiding their children in religious affairs, in spiritual relationships, instilling religious teachings and introducing them to the world.